Biodegradable vegetable oil polymer as a multifunctional lubricating oil additive. Issue 4 (2nd April 2020) - Talukdar, Sujit; Ghosh, Pranab
Abstract: Homopolymer of rice bran oil and its copolymer with dodecyl acrylate and styrene were synthesized and characterized by spectral (NMR, IR), thermogravimetric analysis and gel permeation chromatographic methods. Performance of these polymers was evaluated by standard ASTM methods in base oil and showed very effective as pour point depressants and viscosity modifiers. Biodegradability of all these polymers was tested which showed excellent results. A comparison of their performances has also been evaluated and reported. Abstract : The copolymers showed biodegradability in addition to the multifunctional additive performance (PPD and VM), and so are considered as being more useful in field applications compared to the existing conventional additives.